Pengembangan Sistem Pengumpulan Minyak Jelantah Berbasis Web dan Embedded di Kota Malang - Adelia Tri Caeserine Pinem; Fajar Pradana; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Cooking oil is one of the needs of community in their daily needs. The result of cooking oil that is no longer necessary is called used cooking oil. The amount of production and consumption of cooking oil, the availability of used cooking oil is increasingly abundant. The activity of collecting used cooking oil is still considered inefficient in the collection of used cooking oil, which is carried out by collectors of used cooking oil. Based on a survey that has been conducted at a business place, used cooking oil is picking up once a month while in one week in the place. That business can produce 3 jerry can. Due to supporting the collecting of used cooking oil and make it more efficient, a web-based cooking oil collection system was created by applying the concept of internet of things in it. The concept of the internet of things was built using the ESP8266 NodeMCU module and water level sensor which work with the MQTT network protocol as a means of data communication. This device will be used to detect the level of used cooking oil in the reservoir, which is then converted into data, then collected and processed in the used cooking oil pickup system web. To be able to find out the validity of this system, several testing stages were carried out. The results of these tests indicated that this system functional test is valid, which means that the system can operate properly.